1988
DOI: 10.1161/01.cir.78.1.214
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of canine embolic pulmonary hypertension with recombinant tissue plasminogen activator. Efficacy of dosing regimes.

Abstract: We investigated effects of two dosing regimes of recombinant tissue plasminogen activator (rt-PA) and sodium heparin on pulmonary thrombolysis in a canine model of pulmonary hypertension, induced by injection of radioactive blood clots. By continuously counting over both lung fields with a mobile gamma camera, we correlated rate and extent of pulmonary thrombolysis with corresponding pulmonary hemodynamics. Treatment with heparin, over a 3-hour interval, did not result in significant thrombolysis or in a decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…As cited above, a recent study of embolic pulmonary hypertension demonstrated increased rate of clot lysis with rt-PA15 versus rt-PA90.5 To extend this work, the present study also tests the hypothesis that if the same total dose of rt-PA is given over 5 (rt-PA5) versus 15 (rt-PA15) minutes, the initial rate of thrombolysis and improvement in PAP would be most rapid with the former regimen.…”
mentioning
confidence: 62%
“…As cited above, a recent study of embolic pulmonary hypertension demonstrated increased rate of clot lysis with rt-PA15 versus rt-PA90.5 To extend this work, the present study also tests the hypothesis that if the same total dose of rt-PA is given over 5 (rt-PA5) versus 15 (rt-PA15) minutes, the initial rate of thrombolysis and improvement in PAP would be most rapid with the former regimen.…”
mentioning
confidence: 62%
“…23 We chose to deliver the maximal amount of drug used in the treatment of myocardial infarction (100 mg) in the shortest period supported by the literature -15 minutes. 10,11,38 We also stipulated that patients receive a further 15 minutes of CPR after the infusion. We elected to leave the decision to administer heparin, aspirin, or both to the discretion of the attending physician and found that 5 of the 13 patients who were admitted were given heparin, 4 of whom also received aspirin.…”
Section: Discussionmentioning
confidence: 99%
“…Both theoretical reasoning and studies in laboratory animals support the hypothesis that fibrinolytic agents could be effective during CPR. [10][11][12][13][14] Many studies have suggested that the administration of fibrinolytic agents during CPR can have a dramatic effect, [15][16][17][18][19][20][21][22][23][24][25] but there have been no randomized trials of this approach. We undertook this study to evaluate the effect of the administration of tissue plasminogen activator (t-PA) during CPR in adults with undifferentiated pulseless electrical activity (i.e., with an unknown or presumed cardiovascular cause) that was not responsive to initial therapy.…”
mentioning
confidence: 99%
“…No animal experiments have been performed evaluating the dosing of tenecteplase in pulmonary embolism. Other thrombolytic agents have been evaluated in large animal models of acute pulmonary embolism, providing at least some guidance for human use [24,25]. We think it is important to assess the dosing of tenecteplase specifically for patients with pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%